Comparative features and outcomes of cardiogenic shock in patients with and without prior resuscitated shockable cardiac arrest: Insight from the FRENSHOCK multicenter prospective registry - Hamid Merdji; Vincent Bataille; Anais Curtiaud; Laurent Bonello; François Roubille; Bruno Levy; Pascal Lim; Jean-Claude Dib; Julien Maizel; Nicolas Brechot; Marion Beuzelin; Emmanuelle Fillippi; et al. (Resuscitation Plus)
Aim: Differences between cardiogenic shock (CS) with and without prior resuscitated cardiac arrest (CA) remain largely unexplored. We hypothesized that patients who experience shockable CA followed by CS are likely to have worse outcomes compared to CS without prior CA. Methods: FRENSHOCK is a prospective multicenter observational registry conducted in French critical care units in 2016, which included CS from various etiologies. Patients admitted after resuscitation of a CA were included if they fulfilled previously defined CS criteria. Non-shockable rhythms at the time of medical intervention were considered exclusion criteria and were not recorded in the registry. Results: Among the 771 enrolled patients (mean age 65.7 ± 14.9 years; 71.5 % male), 79 (10.2 %) had a resuscitated shockable cardiac arrest just before inclusion. Shockable CA patients had more respiratory support (78.5 % vs. 33.2 %, p < 0.001), more mechanical circulatory support (35.4 % vs. 16.5 %, p < 0.001), more coronary angiography performed (76 % vs. 48.8 %, p < 0.001), finding more mono-troncular lesions (39 % vs. 16.9 %, p < 0.001). Thirty-day and one-year survival were similar between groups. Among 30-day survivors, CS with an initial shockable CA exhibited significantly improved long-term survival compared to CS without prior resuscitated CA. Conclusion: In a cohort of patients with cardiogenic shock from various etiologies, approximately 10% had experienced prior resuscitation following a cardiac arrest with shockable rhythms. Our findings suggest that selected cardiac arrest with a shockable rhythm leading to cardiogenic shock does not inherently confer a worse prognosis compared to other causes of cardiogenic shock.